Development and Translation of PEDOT:PSS Microelectrodes for Intraoperative Monitoring. (12th May 2017) - Ganji, Mehran; Kaestner, Erik; Hermiz, John; Rogers, Nick; Tanaka, Atsunori; Cleary, Daniel; Lee, Sang Heon; Snider, Jospeh; Halgren, Mila; Cosgrove, Garth Rees; Carter, Bob S.; Barba, David; et al.
Abstract: Recording neural activity during neurosurgical interventions is an invaluable tool for both improving patient outcomes and advancing our understanding of neural mechanisms and organization. However, increasing clinical electrodes' signal‐to‐noise and spatial specificity requires overcoming substantial physical barriers due to the compromised metal electrochemical interface properties. The electrochemical properties of poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) based interfaces surpass those of current clinical electrocorticography electrodes. Here, robust fabrication process of PEDOT:PSS microelectrode arrays is demonstrated for safe and high fidelity intraoperative monitoring of human brain. PEDOT:PSS microelectrodes measure significant differential neural modulation under various clinically relevant conditions. This study reports the first evoked (stimulus‐locked) cognitive activity with changes in amplitude across pial surface distances as small as 400 µm, potentially enabling basic neurophysiology studies at the scale of neural micro‐circuitry. Abstract : The superiority of organic electrodes in mapping human brain activity under various clinical conditions is demonstrated. The improved electrode characteristics allow recording of changes in cognitive activity on the sub‐millimeter scale. The great spatial specificity possible with poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) microelectrodes and the reliable discrimination between and within language modalities underscore PEDOT:PSS's potential for standard electrocorticography clinical practice to maximize outcome for patient care.